1999
DOI: 10.1613/jair.614
|View full text |Cite
|
Sign up to set email alerts
|

Popular Ensemble Methods: An Empirical Study

Abstract: An ensemble consists of a set of individually trained classifiers (such as neural networks or decision trees) whose predictions are combined when classifying novel instances. Previous research has shown that an ensemble is often more accurate than any of the single classifiers in the ensemble. Bagging (Breiman, 1996c) and Boosting (Freund and Shapire, 1996; Shapire, 1990) are two relatively new but popular methods for producing ensembles. In this paper we evaluate these methods on 23 data sets using both neura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
1,176
0
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,347 publications
(1,272 citation statements)
references
References 37 publications
14
1,176
0
14
Order By: Relevance
“…It can be seen that the TER may vary due to the variation of the testing data, even if the size of the data set remains the same. Therefore, standard 10-fold cross validations have been used for result presentation [7]- [12]. In the cross validation, initially available training patterns were partitioned into 10 equal or nearly equal sets, and for each turn, one set was reserved as a testing set, while the remaining nine sets were used for constructing DTs.…”
Section: A Benchmark Problems and General Experimental Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…It can be seen that the TER may vary due to the variation of the testing data, even if the size of the data set remains the same. Therefore, standard 10-fold cross validations have been used for result presentation [7]- [12]. In the cross validation, initially available training patterns were partitioned into 10 equal or nearly equal sets, and for each turn, one set was reserved as a testing set, while the remaining nine sets were used for constructing DTs.…”
Section: A Benchmark Problems and General Experimental Methodologymentioning
confidence: 99%
“…A fixed number of 10 DTs were constructed for an ensemble, except for DECORATE. Previous studies have revealed that ensemble with this number of classifiers is able to show good generalization [7], [18], [19]. To be comparable to the other methods, the maximum number of DTs per ensemble in DECORATE was defined as 10 and the maximum number of trial DTs was 15.…”
Section: A Benchmark Problems and General Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have studied ensemble techniques and diversity measures. Hansen and Salamon have provided the theoretical basis on ensemble [5], while Opitz and Maclin have performed empirical ensemble experiments comprehensively [6]. Zhou et al have analyzed the effect on the number of participating classifiers into ensemble in both theoretical and empirical studies [7].…”
Section: Introductionmentioning
confidence: 99%